Revisiting Local Regulation of Sukabumi Regency No. 7 of 2015 Concerning the Prohibition of Alcoholic Drinks - Miharja, Deni; Ruswanda, Asep Sandi; Ruslan, Idrus (al-'adalah, 2021)
This study discusses the Regional Regulation of Sukabumi Regency Number 11 of 2005 concerning the Control of Alcoholic Beverages and analyzes it through universal human rights principles as stated in the International Covenant on Civil and Political Rights (ICCPR). The aim is to examine whether the regulation is in line with basic human rights principles. This research is a case study using a normative approach. Data were obtained from available documents which then are compared one to another. Based on the results of the study, it is found that the Regional Regulation of Sukabumi Regency tends to be discriminatory, in the sense that it only accommodates the interests of certain religious or belief groups and ignores the interests of other religious or belief groups. The results of this study conclude that the Regional Regulation referred to is not following universal human rights principles as stated in the ICCPR and which has also been ratified by the Government of the Republic of Indonesia through Law No. 12 of 2005 concerning freedom of religion or belief. The government should pay more attention to other crucial issues such as education, health, and public welfare, rather than getting lost in unimportant issues.